Does Corporate Governance Structures Predict Firm’s Market Value? Empirical Evidence from Ghana - Ahulu, Helena; MacCarthy, John (International Journal of Economics and Financial Issues, 2019)
This paper examined the effect of corporate governance structures on the market value of firms in Ghana. Quantitative data was collected on thirty-one firms listed on the Ghana Stock Exchange from 2009 to 2018 to predict the effect of corporate governance structures on the firm’s market value. Panel data regression analysis revealed that corporate governance structures accounted for 84.9% of the variation of a firm’s market value for the period. Furthermore, the study revealed a significant relationship between CEO duality, Non-executive director, board size and firm’s profitability and value. The study concludes that firms should separate CEO position from board chairman position to enhance a firm’s profitability and value. Keywords: Agency theory, Board size, Corporate governance, Duality, Firms JEL Classifications: G32, G34, O16 DOI: https://doi.org/10.32479/ijefi.8874